1984
DOI: 10.1128/jb.159.2.605-610.1984
|View full text |Cite|
|
Sign up to set email alerts
|

Voltage clamp effects on bacterial chemotaxis

Abstract: To examine whether or not sensory signaling in bacteria is by way of fluctuations in membrane potential, we studied the effect of clamping the potential on bacterial chemotaxis. The potential was clamped by valinomycin, a K+-specific ionophore, in the presence of K+. Despite the clamped potential, sensory signaling did occur: both Escherichia coli and Bacillus subtilis cells were still excitable and adaptable under these conditions. It is concluded that signaling in the excitation and adaptation steps of chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…However, chemotactic responses of E. coli to aspartate are not mediated by any such long-range signaling system. Chemotactic responses of E. coli to serine are normal under valinotnycin-induced voltage clamp, indicating that these responses also are not mediated by changes in membrane potential (39).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, chemotactic responses of E. coli to aspartate are not mediated by any such long-range signaling system. Chemotactic responses of E. coli to serine are normal under valinotnycin-induced voltage clamp, indicating that these responses also are not mediated by changes in membrane potential (39).…”
Section: Discussionmentioning
confidence: 97%
“…Signals that have been proposed include membrane potential (64), free calcium ion (44), cyclic GMP (15), and transmembrane ion fluxes (34,64). Several studies have shown that membrane potentials are not likely to be involved in signaling in E. coli (39,43,61), although this mechanism remains viable for some longer bacteria, e.g., spirochetes (24,25).…”
mentioning
confidence: 99%
“…In bacterial chemotaxis it is still controversial whether or not changes in the membrane potential are involved in the sensory transduction. Voltage clamp effects indicate that the information transduction to the flagellar motors does not require electrical steps (157).…”
Section: Halobacterium Sppmentioning
confidence: 99%
“…In order to study electrogenic properties of bacterial membrane proteins, the proteins are usually cloned and expressed in Xenopus oocytes, which removes the downstream effects seen in the native cells (Schmies et al, 2001 ). The role of membrane potential in prokaryotic cell signaling is well known, but not fully understood (Szmelcman and Adler, 1976 ; Margolin and Eisenbach, 1984 ; Ordal, 1985 ; Tisa et al, 1993 ). When elucidated, the mechanisms used by bacteria to regulate membrane potential may help shed light on evolution of memory, olfaction, and other complex functions (Eisenbach, 1982 ; Eisenbach et al, 1983a , b ; Goulbourne and Greenberg, 1983 ; Vladimirov and Sourjik, 2009 ; Lyon, 2015 ).…”
Section: Introductionmentioning
confidence: 99%